Development of An E-Pocket Book Using The Canva Application to Train Students Scientific Literacy Skills - Komaria, Siti; Al habib, Ismul Mauludin; Putri, Hanif Rafika (Jurnal Paedagogy, 2025)
This study aims to develop a Canva-based e-pocket book for enhancing science literacy skills among students. The Research and Development (R&D) method was employed, utilizing the ADDIE model. This study concentrates on developing science literacy skills in conjunction with Biology curriculum materials, particularly in the chapter concerning plant organs, which necessitates comprehension of scientific concepts and their practical application in daily life. The instruments consisted of validation questionnaires, science literacy tests, and interviews. Data analysis involved qualitative descriptive and quantitative statistical analysis. Results showed showed that the e-pocket book media was very feasible (89.7%) and effective in improving students’ science literacy skills with the category of "moderate" (0.4) in the aspect of science context, "high" (0.8) in the aspect of science content and "high" (0.9) in the aspect of science competence. The e-pocket book created using the Canva application can be accessed by anyone even if they don’t have the Canva application, and can be accessed via smartphone, computer and laptop. E-pocket book media can be an innovative learning alternative that effectively in addressing the contraints of educational facilities in schools, thereby potentially enchancing the quality of learning signicantly.